2016
DOI: 10.1007/s40093-016-0138-2
|View full text |Cite
|
Sign up to set email alerts
|

Fruiting bodies yield of oyster mushroom (Pleurotus columbinus) as affected by different portions of compost in the substrate

Abstract: Purpose A study was conducted to assess production of Pleurotus columbinus mushroom fruiting bodies for different formulations of rice or corn straw substrates mixed at different percent portions with the corresponding composted straw. Methods These formulations were: (1) raw straw (RS) mixed with 5 % composted straw (CS), (2) RS mixed with 10 % CS, (3) RS mixed with 15 % CS, (4) RS mixed with 25 % CS, (5) RS mixed with 50 % CS, and (6) 100 % RS. Composted straw (CS) was made of moistened chopped RS mixed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…Chang and Wasser (2017) state that the breakdown of raw ingredients by microorganisms in a fermentation process is more dynamic in a conducive environment. Mohamed et al (2016) state that in the fermentation process, microorganisms propagate and the nutritive substances of the substrate are accumulated in the form of protein and other useful compounds. Therefore, the effects of fertilizer supplement to the EFB substrate on improving the fermentation dynamics in this research was quite clear.…”
Section: Chemical Decomposition Of Efbmentioning
confidence: 99%
“…Chang and Wasser (2017) state that the breakdown of raw ingredients by microorganisms in a fermentation process is more dynamic in a conducive environment. Mohamed et al (2016) state that in the fermentation process, microorganisms propagate and the nutritive substances of the substrate are accumulated in the form of protein and other useful compounds. Therefore, the effects of fertilizer supplement to the EFB substrate on improving the fermentation dynamics in this research was quite clear.…”
Section: Chemical Decomposition Of Efbmentioning
confidence: 99%
“…The data indicated that to obtain good fruitbody yield the spent substrate should be replenished with the easily digestible ingredients like soluble sugar, starch and hemicellulose, but extra nitrogen source (e.g., soymeal), lignocellulosic ingredients were not required to be supplemented, hence wheat bran, cornmeal and T. molitor feces could satisfy this purpose. In fact, too much nitrogen in the substrate can lead to ammonia accumulation during storage or preparation which inhibited mycelial growth (Choi 2004;Mohamed et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed to the mycelia content of mushroom remaining in the spent. It would need a bio-decomposing to be available for the current growing mushroom (Mohamed et al, 2016). Okhuoya et al (2000) reported that a well-balanced carbon to nitrogen ratio enhances the growth and development of mushroom while an imbalance of C/N impedes their growth.…”
Section: Discussionmentioning
confidence: 99%